The role of multiple ionization in fast highly charged ions collisions on H2O - Bachi, Nicolás (2020)
An adaptive classical trajectory Monte Carlo model that explicitly considers the eight electrons cor-responding to the valence molecular orbitals of the H2O molecule is introduced. In this dynamical model, the electrons' binding energies change throughout the collision ensuring the proper energy deposition by the projectile for multiple electron removal. Present results are relevant to the ion-therapy program, specially at irradiation planning stages in which detailed information on the electronic emission spectra are needed as input data.